Elaboration and characterization of curcumin-loaded Tri-CL-mPEG three-arm copolymeric nanoparticles by a microchannel technology - Wu W; Wu J; Fu Q; Jin C; Guo F; Yan Q; Yang Q; Wu D; Yang Y; Yang G (International Journal of Nanomedicine, 2019)
Wenchao Wu,1,2 Jiangqing Wu,1 Qiafan Fu,1 Chenhao Jin,1 Fangyuan Guo,1,2 Qinying Yan,1,2 Qingliang Yang,1,2 Danjun Wu,1,2 Yan Yang,1,2 Gensheng Yang1,21College of Pharmaceutical Science, Zhejiang University of Technology, Hangzhou 310014, People’s Republic of China; 2Research Institute of Pharmaceutical Particle Technology, Zhejiang University of Technology, Hangzhou 310014, People’s Republic of ChinaPurpose: Clinical applications of curcumin (Cur) have been greatly restricted due to its low solubility and poor systemic bioavailability. Three-arm amphiphilic copolymer tricarballylic acid-poly (ϵ-caprolactone)-methoxypolyethylene glycol (Tri-CL-mPEG) nanoparticles (NPs) were designed to improve the solubility and bioavailability of Cur. The present study adopted a microchannel system to precisely control the preparation of self-assembly polymeric NPs via liquid flow-focusing and gas displacing method.Methods: The amphiphilic three-arm copolymer Tri-CL-mPEG was synthesized and self-assembled into nearly spherical NPs, yielding Cur encapsulated into NP cores (Cur-NPs). The obtained NPs were evaluated for physicochemical properties, morphology, toxicity, cellular uptake by A549 cells, release in vitro, biodistribution, and pharmacokinetics in vivo.Results: Rapidly fabricated and isodispersed Cur-NPs prepared by this method had an average diameter of 116±3 nm and a polydispersity index of 0.197±0.008. The drug loading capacity and entrapment efficiency of Cur-NPs were 5.58±0.23% and 91.42±0.39%, respectively. In vitro release experiments showed sustained release of Cur, with cumulative release values of 40.1% and 66.1% at pH 7.4 and pH 5.0, respectively, after 10 days post-incubation. The results of cellular uptake, biodistribution, and in vivo pharmacokinetics experiments demonstrated that Cur-NPs exhibited better biocompatibility and bioavailability, while additionally enabling greater cellular uptake and prolonged circulation with possible spleen, lung, and kidney targeting effects when compared to the properties of free Cur.Conclusion: These results indicate that Tri-CL-mPEG NPs are promising in clinical applications as a controllable delivery system for hydrophobic drugs.Keywords: A549 cells, amiphiphilic three-arm copolymer, biodegradable nanoparticles, biodistribution, pharmacokinetics